New Diaptomidae records (Crustacea: Copepoda: Calanoida: Diaptomidae) in the Neotropical region - Previattelli, Daniel (2013)
TIn this study we present 208 new diaptomids records, including 36 species from 10 genera. They are the result of new samplings as well as of the revision of samples from previous surveys from various localities in the Neotropical Region. In an attempt to clear elucidate about the species ranges we gathered all biogeographically important data and present them here, with comments about the relevance of each record to the understanding of the distribution of the group. © 2013 Check List and Authors.